Kajian operasional layanan transportasi laut terhadap kepuasan penumpang pada Pelabuhan Murhum Kota Baubau - Haruju, Rahma; Badaron, St Fauziah; Syafei, Ilham (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Indonesia is an archipelagic country and is one of the largest maritime countries in the world where 2/3 of its territory is water (sea), so sea transportation has an important role for archipelagic countries. The role of sea transportation cannot be avoided, because sea transportation drives the mobility of passengers, goods and services within and outside the country. Transportation of passengers, goods and services is more efficient by sea than by land and air because the carrying capacity of ships is greater than that of land and air vehicles. Baubau City has a very strategic location in Indonesia’s maritime shipping lanes. In Baubau City itself, sea transportation is the most popular mode of transportation because ships have great access to various corners of Indonesia. Apart from that, ship ticket prices are relatively cheap compared to airplanes. The aim of this research is to analyze the operational influence of sea transportation services on passenger satisfaction at the Murhum port in Baubau City and to analyze the satisfaction variables that most dominantly influence passenger satisfaction at the Murhum port in Baubau City. The research method used was qualitative descriptive analysis through a questionnaire with the SPSS application. The sample from the existing population was determined to be 100 respondents. The results obtained were variable X1: Physical evidence of 0.211; X2 Officer Reliability, 114; X3 Officer Responsiveness 0.144; X4 Security Guarantee 0.096; X5 Empathy Attitude 0.141 and X6 Punctuality 0.776. The coefficient number with the most dominant influence is on the variable X6 on timeliness with a value of 0.776 which has an influence in the strong category. This is because the ship’s departure and arrival schedule is on time.